1997
DOI: 10.1002/pro.5560060612
|View full text |Cite
|
Sign up to set email alerts
|

Secondary and tertiary structural changes in γδ resolvase: Comparison of the wild‐type enzyme, the I11OR mutant, and the C‐terminal DNA binding domain in solution

Abstract: y6Resolvase is a site-specific DNA recombinase (MI 20.5 kDa) in Escherichia coli that shares homology with a family of bacterial resolvases and invertases. We have characterized the secondary and tertiary structural behavior of the cloned DNA binding domain (DBD) and a dimerization defective mutant in solution. Low-salt conditions were found to destabilize the tertiary structure of the DBD dramatically, with concomitant changes in the secondary structure that were localized near the hinge regions between the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…The positions of the activating mutations map to the dimer interface region: helix E, the turn leading into it, and the surfaces that it packs against. It had already been noticed when comparing multiple structures that the WT dimer is quite flexible, and nuclear magnetic resonance data showed that helix E is not integral to the folding of the catalytic domain (43, 46, 47). Thus, it seemed likely that activation might involve a rearrangement of helix E relative to the rest of the catalytic domain.…”
Section: Structural Biology Of Serine Resolvasesmentioning
confidence: 99%
“…The positions of the activating mutations map to the dimer interface region: helix E, the turn leading into it, and the surfaces that it packs against. It had already been noticed when comparing multiple structures that the WT dimer is quite flexible, and nuclear magnetic resonance data showed that helix E is not integral to the folding of the catalytic domain (43, 46, 47). Thus, it seemed likely that activation might involve a rearrangement of helix E relative to the rest of the catalytic domain.…”
Section: Structural Biology Of Serine Resolvasesmentioning
confidence: 99%
“…Examples of folding being driven by ligand binding include proteins with disordered domains that are induced to fold on binding DNA (1,23,24), the case of the (unstructured) prodomain of subtilisin being induced to fold when complexed with subtilisin (25,26), and several cases of preferential anion and/or cation binding to the native state of some proteins (23,27), shifting the equilibrium in favor of the folded state. According to the induced-fit model, ligand binding provides the driving forces for folding and the ligand serves as a template for the disordered domain to adopt its final conformation (1,28).…”
Section: Forcing Thermodynamically Unfolded Proteins To Fold 4833mentioning
confidence: 99%
“…Cells were observed using an Olympus BX60 microscope equipped with a UPlan contrast objective (100 × magnification), and images were captured using a SenSys cooled CCD camera (Photometrics). Images were processed using V for Windows (Digital Optics) O. Sensitivity-enhanced, two-dimensional heteronuclear, single-quantum coherence (HSQC) spectra were acquired essentially as described previously (Kay et al, 1992;Pan et al, 1997) using flipback pulses and gradients for water suppression; the INEPT delay was 2.38 ms. NMR data were processed using Felix95 (MSI) and analysed using XEASY (Bartels et al, 1995).…”
Section: Microscopymentioning
confidence: 99%
“…NMR studies NMR studies of MinE 31-88 were performed at 25ЊC on a Varian INOVA 600 MHz spectrometer using samples of approximately 3 mM [U-15 N] MinE 31-88 dissolved in NMR buffer containing 7.5% D 2 O. Sensitivity-enhanced, two-dimensional heteronuclear, single-quantum coherence (HSQC) spectra were acquired essentially as described previously (Kay et al, 1992;Pan et al, 1997) using flipback pulses and gradients for water suppression; the INEPT delay was 2.38 ms. NMR data were processed using Felix95 (MSI) and analysed using XEASY (Bartels et al, 1995).…”
Section: Sequencing and Mass Spectrometrymentioning
confidence: 99%